Menakar Strategi Nazhir Dalam Pengembangan Wakaf Produktif Di Kecamatan Langsa Timur Kota Langsa - Maulana Ira (Formosa Journal of Science and Technology, 2022)
The strategy of waqf management and development determines the size of the productivity. Therefore, Nazhir's strategy in its management is an interesting thing to study, considering the many potential waqf in Langsa City, especially in East Langsa District which is still less productive. This paper intends to discuss Nazhir's strategy in managing productive waqf, the obstacles faced, as well as the efforts that can be taken in its management, as well as good analysis from the institutional, management and management aspects of productive waqf in order to have development and be useful for the wider community. The results of the study show that the nazhir strategy is in accordance with Law Number 41 of 2004. The findings show that there are three obstacles in managing productive waqf, namely: the nazhir paradigm which is still traditional, nazhir's creativity which is still reduced to direct waqf to a more productive sector, and low productivity. not optimal. Nazhir's efforts to manage productive waqf include establishing partnerships with other parties, promoting unproductive waqf land through recitations or community meetings, building a good image of waqf results, and holding trainings to develop the capabilities of the nazhirs. Three aspects that must be considered and are milestones in the progress of waqf, namely aspects of waqf institutions, accounting aspects, and auditing aspects.